STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN SELUMA - Halim, Marah; Husaini, Husaini; Abdullah, Abdullah (UNIB Press, 2018)
This study aims to analyze the factors that support and hinder receipt of local revenue and analyzed the strategies to increase of local revenue in Seluma Regency. The analytical method used is the SWOT analysis to determine the internal factors and external factors as well as the strategies used to improve the local revenue in order to increase the financial independence Seluma.SWOT analysis obtained for internal factors (strengths - weaknesses) was 0.657 and the analysis of external factors (opportunities - threats) is 0.778, so the strategy is in quadrant I in the form of SO strategy that is by utilizing all the power to seize the opportunity as big as or create strategies that use force to take advantage of opportunities that include: involving employees in the implementation of education and training; explore potential sources of tax/levy new; cooperate across local service agency; utilizing advances in information technology; and improve service to taxpayers